Pentingnya Pendidikan Karakter di Indonesia dalam Membangun Moral Bangsa Perspektif Al-Qur’an - Henderi, Ali (Institut Agama Islam Negeri Padangsidimpuan, 2020)
Character education has become an important part of the national education system because character education has been positioned to be one step to cure social ills. For this reason, character education becomes important to learn. This research is a research literature (library) by collecting data from books, articles and journals. The collected research data is described in detail to then be analyzed. And the main focus in this research is about the phenomenon of the character of Indonesian society that has begun to fragile. To answer the moral phenomenon of the declining nation both in the realm of the family and the public, then as an important comparison material would look back on the character education taught by Luqman al-Hakim against his son.